Association between Estimated Pulse Wave Velocity (ePWV) and in-hospital and ICU 28-day mortality in ischemic stroke patients: A retrospective analysis of the MIMIC-IV database - Shuhe Zhao; Mingjie Liu; Minheng Zhang; Hongwei Liu; Xuan Chen; Yu Wang (PLoS ONE, 2025)
Background Ischemic stroke poses a substantial global health burden. Reliable biomarkers for risk stratification in critically ill stroke patients are lacking. This study investigates estimated pulse wave velocity (ePWV), a non-invasive measure of arterial stiffness, as a novel prognostic indicator for mortality in this population. Methods This retrospective cohort study analyzed data from 3,408 adult ischemic stroke patients admitted to the ICU within the MIMIC-IV database. Patients were categorized by ePWV tertiles. The primary outcome was 28-day mortality (in-hospital and ICU). Multivariate Cox regression models were employed to assess the association between ePWV and mortality, adjusting for comprehensive clinical variables. Results Of the 3,408 patients, 481 (14.1%) died within 28 days of hospitalization. Non-survivors demonstrated significantly higher ePWV values (11.19 vs. 10.57, P < 0.001). Multivariate analysis revealed that ePWV was an independent predictor of both in-hospital (HR = 1.16, 95% CI: 1.05–1.28, P = 0.0033) and ICU 28-day mortality (HR = 1.31, 95% CI: 1.16–1.48, P < 0.0001). Subgroup analyses revealed significant interactions between ePWV and atrial fibrillation for in-hospital mortality (P = 0.0498) and mechanical ventilation for ICU mortality (P = 0.0294). For in-hospital mortality, the ePWV-associated risk was higher in patients with atrial fibrillation (HR 1.19, 95% CI: 1.07–1.31) compared to those without (HR 1.10, 95% CI: 0.98–1.23). For ICU mortality, the ePWV-associated risk was higher in patients without mechanical ventilation (HR 1.45, 95% CI: 1.24–1.70) compared to those with (HR 1.26, 95% CI: 1.11–1.44). Conclusion ePWV is a promising biomarker for predicting mortality in critically ill ischemic stroke patients, particularly identifying high-risk subgroups with atrial fibrillation or those not receiving timely mechanical ventilation.